1983
DOI: 10.1103/physrevb.28.5019
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer analysis of the acceptor site for the donated electrons in FeCl3-intercalated graphite compounds

Abstract: Recently it has been shown that electrons donated by the graphite host to the FeC13 intercalate freeze onto selected Fe'+ ions to change them into Fe + ions at low temperatures. We find that this process occurs continuously beginning at approximately 100 K. Two possible explanations of the data are presented. We examine the possibility that the number of donated electrons which are associated with selected iron sites is temperature dependent, and that a free-bound transition occurs as the temperature is lowere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…16 According to the comment by Millman and Kirczenow, 16 a careful reexamination of the spectra of Ohhashi and Tsujikawa 2 shows that there is a noticeable concentration of Fe 2ϩ present in their sample in spite of their claim. Holwein et al 4 have reported that the percent contribution of Fe 2ϩ is 20% for stage-1 FeCl 3 GIC.…”
Section: A Mössbauer Effectmentioning
confidence: 95%
See 2 more Smart Citations
“…16 According to the comment by Millman and Kirczenow, 16 a careful reexamination of the spectra of Ohhashi and Tsujikawa 2 shows that there is a noticeable concentration of Fe 2ϩ present in their sample in spite of their claim. Holwein et al 4 have reported that the percent contribution of Fe 2ϩ is 20% for stage-1 FeCl 3 GIC.…”
Section: A Mössbauer Effectmentioning
confidence: 95%
“…2,4,[12][13][14][15][16] Millman and Kirczenow 16 have shown that there are three kinds of Fe site in the FeCl 3 intercalate layers of stage-1 and stage-2 FeCl 3 GIC's. Their results for stage-2 FeCl 3 GIC are as follows.…”
Section: A Mössbauer Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Mössbauer spectroscopy reveals a more complex situation. Three distinct Fe sites (A, B, and C) are found in temperature-dependent Mössbauer measurements [16,17]. The majority component originates from site A and is attributed to Fe 3+ ions [16], the magnetic moments of which lie in the basal plane [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…Three distinct Fe sites (A, B, and C) are found in temperature-dependent Mössbauer measurements [16,17]. The majority component originates from site A and is attributed to Fe 3+ ions [16], the magnetic moments of which lie in the basal plane [16,17]. This component plays a dominant role in the onset of the low-temperature magnetically ordered state, as only the Fe 3+ ions of site A were found to participate in the magnetic ordering [17].…”
Section: Introductionmentioning
confidence: 98%